The Effect Of Edpuzzle Application On Students’ Speaking Fluency At Seventh Grade Students Of SMPS IT Mutiara - Nabilla, Asa (Jolly Journal of English Education, 2023)
The Objectives of this research are to find out the The Effect of Edpuzzle Application on Students’ Speaking Fluency at Seventh Grade Students of SMPS IT Mutiara in academic year 2019/2020. The researcher used pre-experimental research design with quantitative approach. The population of the research was the students at the seventh grade of SMPS IT Mutiara which has 4 class that divided by boy’s class and girl’s class, each class consisted 30 students but the researcher only choose 1 class by using cluster sampling method, the sample consisted 30 students but only 15 students are able to present at the research learning. Technique of collecting data are by using speaking test. The mean score of the pre-test was 57.40 and the mean score of the post-test was 75.06. It can be concluded that there were differences in the average of the students’ speaking fluency at the time of pre-test and post-test. It mean there was significant difference on students’ speaking fluency by using Edpuzzle Application